The Implementation of Market Service Retribution Policy of Trade and Industry Department of Pekanbaru - hernimawati, hernimawati; sufi, wasiah (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
The market service retribution policy is basically a part of the source of local revenue that is quite necassary which will also determine the level of a region self-development and it can also determine the target of development and the area of development in the future. This study aims to determine the implementation of market service retribution policies in the Department of Trade and Industry of Pekanbaru City along with supporting factors and barriers. The research method used is descriptive method with a qualitative approachment. The theory used is the theory of George C.Edwards III which suggests four indicators that play an important role in achieving successful implementation. The results showed that the implementation of the market service retribution policy in Disperindag Pekanbaru City has shown good results, where policies were implemented in accordance with local regulations that have been made by the Regional Government regarding to The Market Service Retribution. However, lack of human resources as an interpreter or inner worker who is a civil servant because all this time the inner bill is an employee of honorarium, which is worried to commit fraud as well as retribution from the market service and the lack of financial or budgetary resources received due to a lack of awareness retribution in complying with regulations that have been included in the Regional Regulations regarding payment of retribution.